(untitled) (Revista Contexto & Saúde, 2022)
Analyzing a tendency of scientific literature related to environment and respiration disorders during early childhood. A narrative review of research and systematic review articles had published in English, Portuguese, French, and Spanish were selected. All texts were searched LILACS, PubMed / MEDLINE, SCOPUS, EBSCO / CINAHL, EVIP-NET, and Cochrane Library indexed database. In November 2019, three keyords were combined and separated by the boolean operator and/or. Of the 1,702 results, 42 were included for reviewing, published between 1993-2019. After filtering, the articles were evaluated for methodological quality by a doble reviewer and grouped in three decades (1990, 2000, 2010). A trend of an epidemiological model kept three concepts: respiratory condition, environment, and the child’s vulnerability. They elicited the cause and effect of disorders without considering the structural, social, and environmental determinants of critical child health that pose a strong influence on hospitalization due to ambulatory care sensitive conditions. The healthy promotion environment and the reduction of preventable deaths require looking beyond the clinical-epidemiological model. Facing this problem needs to rethink the way of producing knowledge, articulating health, and the environment.